2014
DOI: 10.1155/2014/450734
|View full text |Cite
|
Sign up to set email alerts
|

Role of Working Memory Storage and Attention Focus Switching in Children’s Comprehension of Spoken Object Relative Sentences

Abstract: The present study evaluated a two-mechanism memory model of the online auditory comprehension of object relative (OR) sentences in 7–11-year-old typically developing children. Mechanisms of interest included working memory storage (WMS) and attention focus switching. We predicted that both mechanisms would be important for comprehension. Forty-four children completed a listening span task indexing WMS, an auditory attention focus switching task, and an agent selection task indexing spoken sentence comprehensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 65 publications
1
13
1
4
Order By: Relevance
“…In the developmental literature, it has been suggested that the poorer comprehension of noncanonical sentences compared with canonical sentences is attributable to storage differences between the two structures, with noncanonicals (not canonicals) involving the storage of two unintegrated NPs until processing the critical verb (Felser, Marinis, & Clahsen, 2003;Finney et al, 2014;Weighall & Altmann, 2011). Our findings, however, lead us to a more nuanced view of the role of cWM.…”
Section: Td Groupcontrasting
confidence: 48%
See 2 more Smart Citations
“…In the developmental literature, it has been suggested that the poorer comprehension of noncanonical sentences compared with canonical sentences is attributable to storage differences between the two structures, with noncanonicals (not canonicals) involving the storage of two unintegrated NPs until processing the critical verb (Felser, Marinis, & Clahsen, 2003;Finney et al, 2014;Weighall & Altmann, 2011). Our findings, however, lead us to a more nuanced view of the role of cWM.…”
Section: Td Groupcontrasting
confidence: 48%
“…Such findings suggest that the comprehension of even simple grammar by children with DLD is not yet automatic. There is also evidence implying that attention switching is important to TD children's sentence comprehension (Finney, Montgomery, Gillam, & Evans, 2014). Children listened to object relative sentences (The goat [i] that the pig had bumped [ti] near the bush was smiling) and selected the agent of the sentence from two images (agent, patient) presented after the embedded verb/ syntactic gap [ ti ].…”
Section: Influence Of Cognitive Processing On Sentence Comprehensionmentioning
confidence: 99%
See 1 more Smart Citation
“…We might argue that the comprehension of such structures invites attention switching because children must momentarily switch their focus of attention away from the demands of current linguistic processing (e.g., processing embedded VP) to WM to reactivate NP1. Finney, Montgomery, Gillam, and Evans (2014) provided the first empirical evidence that focal attention switching is a significant predictor of TD children's real-time OR sentence comprehension (The goat i that the pig had bumped [t i ] near the bush was smiling). The authors argued that children must momentarily redirect their attention from processing the embedded verb (bumped) to WM to reactivate NP1 (the goat) to establish a long-distance syntactic dependency.…”
Section: Phase 1: Psychometric Modeling Studiesmentioning
confidence: 99%
“…Working memory (WM) refers to the processing of information while maintaining that information in temporary storage. Prior research has established the importance of WM in typical language processing by adults and children [ 9 13 ] as well as in children with language impairment [ 14 17 ]. While both verbal and nonverbal WM has been investigated in children with SLI and ASD, most of the research examining the association between WM and grammatical processing has employed verbal WM tasks.…”
Section: Introductionmentioning
confidence: 99%